Mapping, Characterization and Acceleration of Apache Spark Applications - Σταμέλος, Ιωάννης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Τεχνολογίας Πληροφορικής και Υπολογιστών. Εργαστήριο Μικροϋπολογιστών και Ψηφιακών Συστημάτων VLSI, 2017)
Emerging web applications like big data analytics have significantly increased the workload on the data centers during the last years. In 2015, the total network traffic of the data centers was around 4.7 Exabytes and it is estimated that by the end of 2018 it will cross the 8.5 Exabytes mark. The growing demands both in performance and energy efficiency, have led companies into charting new paths for developing energy-efficient platforms for heterogeneous datacenters, therefore they recently started deploying FPGA accelerators and further offloading part of the workload to embedded processors (i.e. ARM processors) at a datacenter scale.